The Relationship Between Character Education in Schools and Social Awareness in Sustainable Development - Judijanto, Loso; Suherlan; Purnama, Yulian (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Character education in schools is one of the key elements in shaping a generation that is not only academically intelligent but also possesses strong moral values. This education instills various positive values such as integrity, discipline, responsibility, empathy, and honesty, which are expected to shape students' personalities into moral individuals who contribute positively to society. This research aims to examine the extent to which character education in schools can influence students' social awareness, which they then implement in their lives as members of society. This study employs a literature review method with a qualitative approach, aimed at adding references related to community service. The data collection process was carried out by searching for scholarly articles published between 2014 and 2024, with Google Scholar as the primary source. The results of the study show that character education in schools plays a crucial role in shaping social awareness, which contributes to sustainable development. By instilling character values such as responsibility, empathy, and environmental concern, students are not only prepared to become academically successful individuals but also caring and responsible citizens. Programs such as "Sekolah Adiwiyata" and social initiatives in schools provide concrete evidence that character education can encourage students to actively participate in social and environmental activities, thereby strengthening social awareness within their communities. Thus, character education can be regarded as a foundation for a sustainable future.